Crystalline salts of a diuretic drug torasemide with improved solubility and dissolution properties. Issue 23 (27th May 2022) - Garg, Monika; Singh, Mayank K.; Koli, Saylee Manohar; Sreedhar, Bojja; Ramakrishna, Sistla; Nanubolu, Jagadeesh Babu
Abstract : Two novel pharmaceutical crystalline salts of a diuretic drug torasemide with improved solubility and dissolution profiles are disclosed in this manuscript. Abstract : Torasemide is a loop diuretic drug. The poor aqueous solubility of the drug is of concern and there is a need to improve its properties. Pharmaceutical salt formation is a promising approach for solubility enhancement. Except for the HCl salt, there are no reports on the salts of torasemide and systematic studies of solubility improvements are also lacking. Three novel crystalline salts have been identified which are torasemide fumarate, torasemide oxalate and torasemide oxalate methanol solvate. The crystalline salts are characterized by crystallographic (SCXRD and PXRD), spectroscopic (FT-IR and NMR) and thermal (DSC, TGA and HSM) methods. The expected drug–coformer stoichiometry (2 : 1 or 1 : 0.5) is achieved only in the case of the torasemide oxalate crystalline salt (1 : 0.5) whereas torasemide fumarate crystallizes in a 1 : 1 drug–coformer stoichiometry. The methanol solvate of torasemide oxalate represents a special situation. It crystallizes in a 2 : (0.5 + 0.5) drug–coformer stoichiometry, wherein the two independent half molecules of oxalate anions are, although chemically the same, crystallographically distinct, conceptually being a Z ′ = 2 structure. These results indicate that besides fulfilling the complementarities of acid–base functionalities for effective salt formation, other factors like accommodation of drug and coformer molecules in the crystal lattice through adjustments in their stoichiometry, conformational variations, hydrogen bonds, and solvent of crystallization could play a critical role in the development of energetically favourable crystalline solids. Compared to the parent torasemide drug, the salts have shown enhanced solubility profiles (18 times for fumarate salt and 14 times for oxalate salt). Similarly, the salts have shown a very rapid dissolution pattern (≥85% in ≤15 minutes) in simulated gastric fluid (pH 1.2) and phosphate buffer medium (pH 6.8) whereas the dissolution of the T-I polymorph of torasemide is only 57% in simulated gastric fluid and 66% in phosphate buffer. The crystalline salts of torasemide with improved solubility and dissolution profiles may find their applications in the development of formulations where a rapid onset of diuretic effect is desired.